Investment: International investment and local food security - Zhan, James; Mirza, Hafiz; Speller, William (International Food Policy Research Institute, 2018)
International investments in agriculture have a broad range of social, economic, and environmental impacts. At their best, they create decent jobs that upgrade local skills, provide local farmers with incomes, improve access to markets and finance, develop rural infrastructure and introduce new technologies to modernize domestic sectors, create new sources of food security, and generate lasting, mutually beneficial partnerships with surrounding communities. At worst, investments result in the displacement of people, are detrimental to existing sources of food security, lead to violent conflicts with local communities, damage the natural environment, fail to generate promised benefits for the host country, and themselves fail financially, with companies exiting the host country and leaving a void in their wake.